Feedback - Gomes, Fabio; Schuftan, Claudio; Tudge, Colin (World Nutrition, 2013)
Fabio Gomes KitKat goes android Claudio Schuftan scolds The Lancet child malnutrition series Colin Tudge says that ‘golden rice’ is a public relations stunt